KERJASAMA UNITED STATES AGENCY FOR INTERNATIONAL DEVELOPMENT (USAID) DAN INDONESIA DALAM MENCAPAI SDGS TUJUAN AKSES AIR BERSIH DAN SANITASI: Studi Kasus Program USAID IUWASH PLUS Di Kabupaten Bogor - RA. Lusika Mustikamaya (2022)
The cooperation between Indonesia and the United States in terms of foreign aid carried out by USAID has existed since 1950, which was carried out to meet the national interests of each country. The establishment of CDCS-Indonesia compiled by USAID and Bappenas shows that both countries have the same interest in being able to realize international development that has been adjusted to the SDGs target. One of the programs that are in line with the SDGs target point number 6 is the program USAID IUWASH PLUS, which aims to help Indonesia achieve universal access in terms of access to clean water and sanitation. The problem with target number 6 is related to other targets, therefore, it is essential to achieve it as soon as possible. In addition, with global warming and increasing population, there is an imbalance between the need and supply of water. The USAID IUWASH PLUS program is implemented directly with local governments in Indonesia. There are 35 regions that are partners in this program, one of which is Kabupaten Bogor.